Pengaruh E-Service Quality terhadap Kepuasan Pelanggan The Why Resort - I Wayan Putu Adityapratama; Ni Luh Gde Sri Sadjuni; Nyoman Gede Mas Wiartha; Ni Desak Made Santi Diwyarthi (Yayasan Literasi Sains Indonesia, 2024)
Customer satisfaction is an evaluation given by customers after making a purchase of a product or service resulting from a comparison of customer expectations with the performance of products and services purchased by customers. The purpose of this study was to determine the effect of e-service quality on customer satisfaction at The Why Resort Bali Hotel. The population in this study involved customers who had used the electronic services of The Why Resort Bali Hotel. The sample in this study amounted to 160 people selected using non-probability sampling technique. This study used primary data, which was obtained through distributing questionnaires to respondents. The analysis method used simple linear regression with SPSS version 23. The results of this study indicate that the e-service quality variable has a significant effect on Customer Satisfaction with a tcount> ttable value of 14.050> 1.975. E-service quality is positive with a beta value of 0.597 on Customer Satisfaction, so increasing e-service quality will increase Customer Satisfaction. E-service quality has a contribution to influence Customer Satisfaction of 55.5% in the moderate category, while the remaining 44.5% is influenced by other variables not examined in this study.